Bioprocess development for (2R, 3R)‐butanediol and acetoin production using very high polarity cane sugar and sugarcane molasses by a Bacillus amyloliquefaciens strain. Issue 7 (17th April 2019) - Maina, Sofia; Mallouchos, Athanasios; Nychas, George‐John E; Freire, Denise MG; de Castro, Aline Machado; Papanikolaou, Seraphim; Kookos, Ioannis K; Koutinas, Apostolis
Abstract: BACKGROUND: Efficient production of (2R, 3R)‐2, 3‐butanediol (BDO) and acetoin using the GRAS strain Bacillus amyloliquefaciens from very high polarity (VHP) cane sugar and sugarcane molasses could lead to the development of a sustainable industrial process. RESULTS: The effect of initial substrate concentration, nitrogen source, temperature, inoculum size and pH were evaluated in shake flask cultures. Batch bioreactor cultures showed that (2R, 3R)‐BDO production (up to 28 g L −1 ) with high yield (up to 0.43 g g −1 ) and productivity (up to 0.93 g L −1  h −1 ) was favored at low k L a values (17–49 h −1 ). Increasing k L a values (63–104 h −1 ) initiated acetoin production (up to 25.6 g L −1 ) with yields up to 0.4 g g −1 and productivities up to 1.42 g L −1  h −1 . Fed‐batch fermentation carried out at k L a value of 49 h −1 with VHP cane sugar resulted in mixed production (127.3 g L −1 ) of (2R, 3R)‐BDO, (2R, 3S)‐BDO and acetoin at 122 h with high yield (0.50 g g −1 ) and productivity (1.04 g L −1  h −1 ). In a similar fed‐batch fermentation with sugarcane molasses, mainly (2R, 3R)‐BDO production (48.7 g L −1 with purity of 87.8%) was achieved at 59 h with yield of 0.4 g g −1 and productivity of 0.83 g L −1  h −1 . At 130 h, (2R, 3R)‐BDO was converted mainly into acetoin (55.4 g L −1 ). CONCLUSION: This study demonstrates that k L a manipulation could be used in batch cultures to divert the bacterial metabolism towards either (2R, 3R)‐BDO or acetoin production. Fed‐batch cultures with sugarcane molasses could lead to either (2R, 3R)‐BDO or acetoin production with negligible by‐product formation. © 2019 Society of Chemical Industry